Quantitative analysis of contrast-enhanced ultrasound in neoadjuvant treatment of locally advanced rectal cancer: a retrospective study - Bai, Gouyang; Wang, Congying; Sun, Yi; Li, Jinghua; Shi, Xiangzhou; Zhang, Wei; Yang, Yilin; Yang, Ruijing (Frontiers in Oncology, 2024)
Purpose: To explore the clinical value of contrast-enhanced ultrasound (CEUS) quantitative analysis in the evaluation and prognosis of neoadjuvant chemoradiotherapy for locally advanced rectal cancer (LARC).Methods: Eighty-three consecutive patients undergoing neoadjuvant chemoradiotherapy and total mesorectal excision for LARC were retrospectively included. According to pathological results, patients were categorized into complete or incomplete response groups. Differences in ultrasonic parameters, pathological results, and clinical data between groups were evaluated.The cutoff point for a complete response as determined by quantitative analysis of CEUS was assessed using a receiver operating characteristic curve; additionally, overall survival (OS) and progression-free survival (PFS) were analyzed.Results: Of the 83 patients, 12 (14.5%) achieved a complete response and 71 (85.5%) did not.There were significant between-group differences in carcinoembryonic antigen (CEA) levels, differentiation degree, proportion of tumor occupying the lumen, anterior-posterior and superior-inferior diameters of the lesion, and intensity of enhancement (P<0.05). CEUS quantitative analysis showed significant between-group differences in peak intensity (PI) and area under the curve (AUC) values (P<0.05). The OS and PFS of patients with high PI, high AUC value, and poorly differentiated cancer were significantly worse than those with low PI, low AUC values, and moderately to highly differentiated cancer (P<0.05). High CEA levels (hazard ratio: 1.02, 95% confidence interval: 1.01-1.04; P=0.002) and low differentiation (2.72, 1.12-6.62; P=0.028) were independent risk factors for PFS and OS.Conclusions: CEUS can predict the response to neoadjuvant treatment in patients with LARC.CEUS quantitative analysis is helpful for clinical prognosis.